State Responsibility in Guaranteeing Access to Essential Medicines for Public Health: Tanggung Jawab Negara dalam Menjamin Akses terhadap Obat Esensial untuk Kesehatan Masyarakat - Hamid, Siti Nur Cholisa; Muis, Lidya Shery (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The availability of essential medicines is a critical determinant of healthcare quality, directly impacting public health needs. Specific Background: In Indonesia, the government is tasked with ensuring these medicines are accessible in adequate quantities, timely, and at affordable prices. Despite existing policies, challenges persist in achieving these objectives, particularly highlighted during the COVID-19 pandemic. Knowledge Gap: There is limited empirical analysis regarding the state’s role and effectiveness in providing essential medicines amidst regulatory frameworks and public health needs. Aims: This study aims to examine the state's responsibilities in ensuring the availability of essential medicines through literature reviews and policy analysis, focusing on relevant legal frameworks, including Law Number 17 of 2023 on health and constitutional provisions. Results: The findings indicate that the state plays a pivotal role in providing essential medicines via mechanisms such as subsidies, price monitoring, and incentives for the local pharmaceutical industry. Challenges in distribution, production capacity, and international collaboration were also identified. Novelty: This research offers a comprehensive overview of the essential medicines landscape in Indonesia, detailing the intersection of legal frameworks and public health requirements. Implications: The study emphasizes the government's need to enhance public access to essential medicines, thereby improving national health quality, and informs policymakers and stakeholders on effective strategies. Highlights: Government responsibility: Ensure essential medicines are accessible and affordable. Policy challenges: Address distribution and production capacity issues. Health impact: Availability affects overall public health outcomes. Keywords: essential medicines, healthcare quality, state responsibility, public health, Indonesia